Agroecological management of fall armyworm using soil and botanical treatments reduces crop damage and increases maize yield - Chawanda, Gift; Tembo, Yolice L. B.; Donga, Trust Kasambala; Kabambe, Vernon H.; Stevenson, Philip C.; Belmain, Steven R. (Frontiers in Agronomy, 2023)
Fall armyworm continues to disrupt smallholder farming systems across sub-Saharan Africa, with sporadic outbreaks and chronic cereal crop losses. Smallholders have been adapting to the pest by increasing crop surveillance for targeted control measures and developing low-cost solutions. For example, some report placing soil or ash in maize whorls where the mechanism of pest control may be suffocation, abrasion leading to desiccation, or through the introduction of soil-borne entomopathogens. To verify the efficacy of this approach we evaluated different soil types on maize infested with fall armyworm to assess their efficacy. We also evaluated the efficacy of pesticidal plant species, powdered and placed in leaf whorls to control fall armyworm. Different USDA-characterised soil types (sand, loam, clay) and wood ash were effective in reducing the number of larvae and maize leaf damage by approximately 50%. Maize yield with the synthetic control (chlorpyriphos) was 13,700 kg/ha, i.e. 42% higher than the untreated control (7,900 kg/ha). Soil and ash treatments yields between 10,400 to 12,400 kg/ha were 24-36% higher than the untreated control. Dry soil applied after watering was most effective regardless of soil type. However, wet soil treatments applied before watering were also highly effective in reducing the number of fall armyworm larvae and reducing insect damage to maize leaves. Botanical powders from Azadirachta indica, Nicotiana tabacum, Cymbopogon citratus and Lippia javanica were also effective when applied to maize leaf whorls. Plant powder treatments and water extracts were significantly effective in reducing the number of larvae and leaf damage. The highest yield obtained with botanicals was observed with A. indica powder (5,600 kg/ha), C. citratus extract (5,800 kg/ha) and N. tabacum extract (5,800 kg/ha), where the synthetic treatment yield was 6,900 kg/ha and the untreated yield was 1,700 kg/ha. We conclude that smallholder farmer innovations in managing fall armyworm are effective low-cost options. Scientific validation of soil treatments and botanicals should help increase the confidence of policy makers and allow knowledge extension services to recommend their use to smallholder farmers, which in turn may reduce reliance on imported synthetic pesticides and improve farmer resilience, circular economies and human and environmental health.